TINJAUAN BAURAN PEMASARAN DI CITY EDGE CAFE JATINANGOR - Sugiarto, Yayan; Alfan Gymnastiar, Muhammad (Akademi Pariwisata NHI Bandung, 2024)
This study aims to analyze the effectiveness of the marketing mix at City Edge Café Jatinangor, focusing on four main elements product, price, place, and promotion. Using a Likert scale, this research evaluates customer perceptions of the performance of each aspect of the marketing mix and identifies areas requiring improvement. The research method used is descriptive, with data collection techniques including the distribution of questionnaires and observation. The results show that the product aspect is rated